Effect of platform configurations and environmental conditions on the performance of floating solar photovoltaic structures - Jifaturrohman, Mohammad Izzuddin; Putranto, Teguh; Utama, I Ketut Aria Pria; Huang, Luofeng (TU Delft OPEN Publishing, 2024)
The growth and development of floating solar photovoltaic (FPV) power plants is a prominent topic within renewable energy technology. One reason contributing to this desired technology design concept is the possibility of land acquisition issues, whereas the usage of the ocean provides a greater technical alternative area. The objective of the research is to present an innovative design for a floating structure, focusing on investigating and comparing the seakeeping performance of several hull configurations: catamaran, trimaran, quadrimaran and pentamaran. The final computational simulation results indicate a linear negative trend in the motion response graphs, particularly in specific significant response values for heave (Global Z), roll (Global RX), and pitch (Global RY), as the hull configuration increases.
Keywords: 4015 Maritime Engineering; 40 Engineering; 7 Affordable and Clean Energy; 13 Climate Action; CFD; Floating photovoltaic; Multi-hull; Renewable energy; Seakeeping characteristics